2009
DOI: 10.1007/s00421-009-1090-x
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with physical activity guidelines in a group of UK-based postal workers using an objective monitoring technique

Abstract: Compliance with physical activity (PA) recommendations was assessed using objective PA monitoring of ambulatory activity, in two healthy groups of individuals with active and sedentary occupations. The study showed generally low compliance with the guidelines (53% with 10,000 steps a day; 10% with 30 min of moderate activity a day; and 1% with 30 min of moderate activity a day in bouts of at least 10 min (ACSM)). Adherence to guidelines decreased as more rigorous conditions were applied to the PA data. Use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 19 publications
2
50
1
Order By: Relevance
“…The consequences of various basic criteria of physical activity assessment, included in health-oriented recommendations, are quite significant differences in PA evalutaion even in the same study group (percentages of compliance with PA guidelines are unlike). A similar trend was observed in research conducted by Chastin et al (2009), Scheers et al (2013 and Chaix et al (2014) where the degree to which a PA recommendation was satisfied differed depending on the criterion used in the evaluation. There are still only few publications investigating this problem.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The consequences of various basic criteria of physical activity assessment, included in health-oriented recommendations, are quite significant differences in PA evalutaion even in the same study group (percentages of compliance with PA guidelines are unlike). A similar trend was observed in research conducted by Chastin et al (2009), Scheers et al (2013 and Chaix et al (2014) where the degree to which a PA recommendation was satisfied differed depending on the criterion used in the evaluation. There are still only few publications investigating this problem.…”
Section: Discussionsupporting
confidence: 57%
“…Additionally during the week of monitoring, a vast majority of participants (98%) took an adequate number of steps to fulfill the recommendation by Tudor-Locke et al (2011). The results of authors' own research are pretty optimistic in the light of those demostrated in another researches (Chastin et al, 2009, Bassett, Wyatt, Thompson, Peters, Hill, 2010Hirvensalo et al, 2011;Biernat, 2011;Colley et al, 2011;Pate et al, 2015). The possible reason of that is the fact that our study looked exclusively on members of health promoting associations, who seem to be more physically active than the general population.…”
Section: Discussionmentioning
confidence: 49%
“…World-wide previous studies revealed that many factors, such as education, age [22], profession [23] marital status [24] or smoking [3], affect the level of PA. For example, the rate of participation in PA increases proportionally to the level of education [3]. Similarly, lower education is connected with a lower income and results in creating more PA barriers [24].…”
Section: Discussionmentioning
confidence: 99%
“…the beneficial influence of physical activity on human health is widely recognized and tested among international researchers [1,2,3,4,5,6,7]. Physical activity should be accepted in a special way among the students as future parents, including mainly among medical faculty students as future doctors and other professions related to health.…”
Section: Introductionmentioning
confidence: 99%